Investigating Students’ Writing Performance and Attitude Towards a Web 2.0-Based Flipped Classroom Instruction - Muluk, Safrul; Dahliana, Syarifah (Jurnal Ilmiah Peuradeun, 2024)
One of the methods gaining popularity in the context of teaching in recent years is flipped classroom instruction (FCI). The FCI encourages EFL learners to maximize their time away from class by using products of advanced technologies. Owing to this fact, the researchers conducted a study on the issue of Students’ writing performance and their attitudes about the use of technology. A mixed-method study was used to investigate students’ writing achievement and their attitudes to web-based instruction in the form of Flipped classroom instruction. Quantitative data was collected through survey questionnaires, while qualitative data was gained from interviews. The investigation on flipped classroom instruction was conducted at three State Islamic Universities in Indonesia. The questionnaires were distributed to EFL students at these three State Islamic universities to identify students’ experience in learning writing by using flipped classroom instruction. There were 198 students involved in this research. Also, twelve English lecturers from those three universities were interviewed. Findings suggested that most students had a positive attitude toward flipped classroom instruction. Although flipped classroom interaction does not guarantee the improvement of students’ writing performance, it is believed that flipped classroom instruction supports students to have a meaningful and effective learning experience.